1973
DOI: 10.1901/jeab.1973.19-251
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF PUNISHING ELEMENTS OF A SIMPLE INSTRUMENTAL‐CONSUMMATORY RESPONSE CHAIN1

Abstract: Rats were trained to press a lever, with every response reinforced with water. After responding was established, nine rats were administered a brief shock after each lever press, and nine others were shocked after drinking. The two procedures resulted in similar suppression of responding, and examination of the latency data when responding was partially suppressed indicated that under both conditions response suppression was due primarily to an increase in the latency of the instrumental response, rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
1

Year Published

1979
1979
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…Whereas our present results agree with those of Church ( 1969 ) showing that instrumental response punishment more effectively suppresses behaviour than consummatory response punishment and De Costa and Ayres ( 1971 ) showing that instrumental responses are more sensitive to conditioned suppression than consummatory responses, they differ from the results of other studies. Thus, Myer ( 1973 ) showed no difference between consummatory and instrumental punishment in their overall effectiveness in suppressing responding. In contrast, Bertsch ( 1972 ) showed that consummatory response punishment was more capable of suppressing behaviour than instrumental punishment.…”
Section: Discussionmentioning
confidence: 93%
“…Whereas our present results agree with those of Church ( 1969 ) showing that instrumental response punishment more effectively suppresses behaviour than consummatory response punishment and De Costa and Ayres ( 1971 ) showing that instrumental responses are more sensitive to conditioned suppression than consummatory responses, they differ from the results of other studies. Thus, Myer ( 1973 ) showed no difference between consummatory and instrumental punishment in their overall effectiveness in suppressing responding. In contrast, Bertsch ( 1972 ) showed that consummatory response punishment was more capable of suppressing behaviour than instrumental punishment.…”
Section: Discussionmentioning
confidence: 93%
“…In Church (1969) shock was administered when the rat inserted its head into the feeder (slightly before the contact with the pellet). In Bertsch (1972) and Myer (1973) the shock happened after the consummatory response was finished. Other technical differences prevent a direct comparison of these studies, such as the length of the response sequence or the intensity of the punishing stimulus (Bertsch, 1976), as well as the type of deprivation imposed on the organism (e.g., water or food), the topography of the consummatory response (Walters & Herring, 1978), the baseline schedule (Myer, 1973), or the length of the punishment phase (Church, 1969).…”
mentioning
confidence: 99%
“…First, there is a theoretical interest concerning whether or not biologically significant or intrinsically reinforcing responses are relatively more resistant to the effects of punishment than are extrinsically reinforced responses (e.g., Estes, 1969;Solomon, 1964). Second, there is concern with how best to punish a response chain or sequence (e.g., Church, 1969;Myer, 1973). Experiments that have directly attempted to ascertain whether punishment of the instrumental or the consummatory response more effectively suppresses ongoing behavior have generally produced conflicting results.…”
mentioning
confidence: 99%
“…For example, Church (1969) and Walker, Popovich, and Derby (Note 1) concluded that punishing the instrumental response suppressed behavior to a greater degree than did punishing the consummatory response. Myer (1973) concluded that there was no difference between punishing these types of responses, while Bertsch (1972) found that punishing the consummatory response more effectively suppressed behavior than did punishing the instrumental response.…”
mentioning
confidence: 99%
See 1 more Smart Citation